Young Orville and Wilbur Wright : first to fly - Woods, Andrew; Beier, Ellen ([Mahwah, NJ] : Troll, 1992)
A simple biography of the brothers who launched the air age in 1903 when their flying machine stayed in the air for twelve seconds.
School Library Journal
3.5
K-3
Keywords: Wright, Orville, -- 1871-1948 -- Juvenile literature; Wright, Wilbur, -- 1867-1912 -- Juvenile literature; Aeronautics -- United States -- Biography -- Juvenile literature; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Aeronautics -- Biography; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Aeronautics -- Biography